Different perspectives on Latin American identity (International Journal of Scientific Research and Management (IJSRM), 2024)
The given research article deals with the discussion of issues concerning the identity of the Latin American people by examining its history and cultural representations as well as modern perceptions. Latin American people had a mixture of cultures in their own identity, as many ethnicities, such as pre-Columbian civilizations, colonial Europe, Africans, and contemporary socio-political movements, influenced them. To undertake this investigation, the study explores diverse multicultural views originating from different regions and people from social, political, and ethnic origins to acquire a perfect understanding of what it means to be a Latin American individual. This is evident in demonstrating the influence of the colonial past, the rich heritage of indigenous and African communities, and the dynamic nature of identity in provoking the problems of the present day as characterized by globalization, immigration, and change in leadership. Based on the case studies of Brazil, Mexico, and Bolivia, the article emphasizes that despite the diverse members of the region’s population, the residents continue to strive to create a united Latin American subject. The conclusion reiterates the authors’ approach to embracing this complex history and the fight for social justice in creating a united and integrated Latin American people.